2023
DOI: 10.1177/10760296221151166
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombin Time and Coagulation Factor IX as Hemostatic Risk Markers for Legg– Calvé–Perthes Disease

Abstract: Background Legg–Calvé–Perthes disease (LCPD) is a pediatric disorder that occurs due to the avascular necrosis of the femoral head and affects the range of motion of the hip in various degrees. Its etiology is still unknown, although it has been associated with coagulation abnormalities, however, the lack of reproducibility in the results in various studies has created a controversy as to whether hemostasis disorders are related to LCPD. On the other hand, there is little information on laboratory studies that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…PT is a routine study in the clinical laboratory, PT has been reported as a good diagnostic marker for LCPD, a lower PT is related to greater hemostatic activity, since less time will be required for thrombus formation (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…PT is a routine study in the clinical laboratory, PT has been reported as a good diagnostic marker for LCPD, a lower PT is related to greater hemostatic activity, since less time will be required for thrombus formation (13,14).…”
Section: Discussionmentioning
confidence: 99%